Ecological Status of Phlebotomine Sandflies (Diptera: Psychodidae) in Rural Communities of Northeastern Algeria - Nacira Kabbout; Djemoi Merzoug; Haroun Chenchouni (Tehran University of Medical Sciences, 2016)
Background: Algeria is among the most affected Mediterranean countries by leishmaniasis due to its large geographic extent and climatic diversity. The current study aimed to determine the ecological status (composition and diversity) of phlebotomine sandfly populations in the region of Oum El Bouaghi (Northeast Algeria). Methods: An entomological survey was conducted during the period May-October 2010 in rural communities of Oum El Bouaghi. Catches of sandflies were carried out using sticky traps in both domestic and peri-domestic environments of 16 sites located beneath two bioclimatic areas, sub-humid and semi-arid. Most of these sites have visceral and/or cutaneous leishmaniasis cases. Results: A total of 1,363 sandflies were captured and identified. They belong to two genera, Phlebotomus and Sergentomyia, and five species. The species Phlebotomus perniciosus, P. perfiliewi and Sergentomyia minuta were constants. Phlebotomus longicuspis was common and P. papatasi was accidental in the study sites. P. perniciosus and P. perfiliewi are the two possible species that contribute in leishmaniasis transmission across the study area due to their high densities (96 and 49 specimens/m²/night, respectively); these two species dominate other species in all study sites. Conclusion: Findings emphasize the key-role played by P. perniciosus, P. perfiliewi and S. minuta in outlining site similarities based on sandfly densities. The study confirms that the more susceptible sites to leishmaniasis, which hold high densities of these sandflies, were located south of the study area under a semi-arid climate.